Optical coherence tomography for the diagnosis of skin cancer in adults - Ferrante di Ruffano, Lavinia; Dinnes, Jacqueline; Deeks, Jonathan J.; Chuchu, Naomi; Bayliss, Susan E.; Davenport, Clare; Takwoingi, Yemisi; Godfrey, Kathie; O'Sullivan, Colette; Matin, Rubeta N.; Tehrani, Hamid; Williams, Hywel C. (Wiley, 2018)
Background: Early accurate detection of all skin cancer types is essential to guide appropriate management and to improve morbidity and survival. Melanoma and squamous cell carcinoma (SCC) are high-risk skin cancers, which have the potential to metastasise and ultimately lead to death, whereas basal cell carcinoma (BCC) is usually localised, with potential to infiltrate and damage surrounding tissue. Anxiety around missing early cases needs to be balanced against inappropriate referral and unnecessary excision of benign lesions. Optical coherence tomography (OCT) is a microscopic imaging technique, which magnifies the surface of a skin lesion using near-infrared light. Used in conjunction with clinical or dermoscopic examination of suspected skin cancer, or both, OCT may offer additional diagnostic information compared to other technologies. Objectives: To determine the diagnostic accuracy of OCT for the detection of cutaneous invasive melanoma and atypical intraepidermal melanocytic variants, basal cell carcinoma (BCC), or cutaneous squamous cell carcinoma (cSCC) in adults. Search methods: We undertook a comprehensive search of the following databases from inception up to August 2016: Cochrane Central Register of Controlled Trials; MEDLINE; EMBASE; CINAHL; CPCI; Zetoc; Science Citation Index; US National Institutes of Health Ongoing Trials Register; NIHR Clinical Research Network Portfolio Database; and the World Health Organization International Clinical Trials Registry Platform. We studied reference lists and published systematic review articles. Selection criteria: Studies evaluating OCT in adults with lesions suspicious for invasive melanoma and atypical intraepidermal melanocytic variants, BCC or cSCC, compared with a reference standard of histological confirmation or clinical follow-up. Data collection and analysis: Two review authors independently extracted all data using a standardised data extraction and quality assessment form (based on QUADAS-2). Our unit of analysis was lesions. Where possible, we estimated summary sensitivities and specificities using the bivariate hierarchical model. Main results: Five studies including 529 cutaneous lesions (273 malignant lesions) were included, providing nine datasets for OCT, two for visual inspection alone, and two for visual inspection plus dermoscopy. Studies were of moderate to poor quality using data driven thresholds for test positivity and giving poor accounts of reference standard interpretation and blinding. Studies may not be representative of populations eligible for OCT in practice, for example due to high disease prevalence in study populations, and may not reflect how OCT is used in practice, for example by using previously acquired OCT images. It is not possible to make summary statements regarding accuracy of detection of melanoma or of cSCC because of the paucity of studies, small sample sizes, and for melanoma differences in the OCT technologies used (high-definition versus conventional resolution OCT), and differences in the degree of testing performed prior to OCT (i.e. visual inspection alone or visual inspection plus dermoscopy). Pooled data from two studies using conventional swept-source OCT alongside visual inspection and dermoscopy for the detection of BCC estimated the sensitivity and specificity of OCT as 95% (95% CI: 91, 97%) and 77% (95% CI: 69, 83%), respectively. When applied to a hypothetical population of 1000 lesions at the mean observed BCC prevalence of 60%, OCT would miss 31 BCCs (91 fewer than would be missed by visual inspection alone and 53 fewer than would be missed by visual inspection and dermoscopy), and OCT would lead to 93 false positive results for BCC (a reduction in unnecessary excisions of 159 compared to using visual inspection alone and of 87 compared to visual inspection and dermoscopy). Authors' conclusions: Insufficient data are available on the use of OCT for the detection of melanoma or cSCC. Initial data suggests conventional OCT may have a role for the diagnosis of BCC in clinically challenging lesions, our meta-analysis showing a higher sensitivity and higher specificity when compared to visual inspection and dermoscopy. However the small number of studies and varying methodological quality means implications to guide practice cannot currently be drawn. Appropriately designed prospective comparative studies are required, given the paucity of data comparing OCT with dermoscopy and indeed other similar diagnostic aids such as reflectance confocal microscopy.